Daily and Latent Lagged Effects of Rainfall on Pedestrian-Vehicle Collisions - António Lobo (2020)
Walking safety has been a primary concern for researchers and authorities, who have developed numerous studies concerning the interaction between pedestrians and vehicles. Nevertheless, few studies have focused on the impacts of weather conditions on pedestrian-vehicle collisions. This research aims at improving knowledge on this subject by investigating the impact of daily precipitation and the lagged effects associated with past accumulated precipitation. Using the city of Porto, Portugal, as a case study, an incremental approach consisting of three models, one Poisson and two negative binomial, was developed to explore the relation between weather conditions and the occurrence of pedestrian-vehicle collisions. The first model accounts exclusively for meteorological variables, providing an insight into the trends of crash frequency under the effects of temperature and precipitation. Then, variables for road classification and land use were introduced in the second and third models, respectively, to account for the diversity of the urban environment. These variables act as proxies for the level of exposure associated with different types of urban space, allowing for a more in-depth understanding of the impacts caused by meteorological conditions. The modeling results show that the number of pedestrian-vehicle collisions tends to increase on rainy days, following the general trend observed in the literature for other types of crashes. Regarding the lagged effects, the results show that the number of pedestrian-vehicle collisions is likely to decrease after a wet week but increases after a wet month.